PERILAKU PEMILIH DALAM PEMILIHAN WALI NAGARI DI KENAGARIAN RABI JONGGOR, GUNUNG TULEH, PASAMAN BARAT, SUMATERA BARAT TAHUN 2014 - Rahmad Mulyadi; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Choosing is an autonomous activity, in the sense of non-pressure and coercion from others. The sociological approach tends to place voting in relation to the social context. The concrete of one's choice in elections is influenced by demographic and socioeconomic backgrounds, such as gender, residence (city-village), occupation, education, class, income and religion. The sociological approach explains, social characteristics and groupings are factors that influence voter behavior.The research method used in this research is descriptive research with qualitative analysis method. This study aims to see how the behavior of voters in the election Wali Nagari in Kenagarian Rabi Jonggor, Mount Tuleh, West Pasaman, West Sumatra Year 2014 that affect the election of one candidate in Pilwana. This study is also to find out how the shift in voter behavior in the context of the social structure of society in Rabi Jonggor kenagarian previously held by other elite groups. So that the influence of various social factors greatly influence voter behavior in determining the choice that make an elite group in government is shifted by other elite group in Kenagarian Rabi Jonggor.The selection of Wali Nagari in Rabi Jonggor Kenagarian Year 2014 shows that the main factor of voters in determining their choice based on sociological approach can be seen from education side, family background or kinship and social class. These three sides determine the voter's behavior in determining the choice because the other side of the sociological approach is not very influential in determining voter behavior, so that the three sides of voter behavior becomes a reference in determining how voters behavior in the election of Wali Nagari Year 2014.Keywords: Pilwana, Nagari, Sociological Approach, Voter Behavior